Comparative performance of lissamine green stains. Issue 1 (February 2018) - Delaveris, Androniki; Stahl, Ulrike; Madigan, Michele; Jalbert, Isabelle
Highlights: A clinical comparison of lid wiper staining between different types of lissamine green impregnated strips was performed. Within subject measurements of lid wiper staining do not significantly differ from day to day. Lid evertion increased lid wiper staining but sequential instillation did not. Lid wiper staining was significantly higher with some lissamine green strips (GreenGlo, OPGreen) than others (Lissaver, Biotech). These findings must be considered when investigating lid wipers, particularly when interpreting a negative finding. Abstract: Purpose: To investigate the performance of lissamine green strips from different manufacturers. Additionally, the repeatability, need for sequential dye instillation and impact of repeated lid evertion on lid wiper staining were assessed. Methods: Study 1 was a prospective, randomised cross-over study where controlled volumes of lissamine green solution prepared from strips (Biotech, Lissaver, GreenGlo, OPGreen) were instilled (right eye: single; left eye: double instillation) on five different days, with OPGreen being tested twice. Lids were everted and digital photographs taken, which were later assessed by a masked observer. Study 2 was an investigator-masked, randomised, controlled study testing the impact of single versus repeated lid evertion. Lid wiper staining was graded (0 to 3 in 0.5 steps). Results: Lid wiper staining differed significantly between lissamine green solutions, with GreenGlo showing the highest amount of staining, and Lissaver the least (all p > 0.009). There were no differences in lid wiper staining over two days, using the OPGreen solution (all p > 0.05). The number of drops instilled (single versus double) did not significantly affect lid wiper staining (all p > 0.05). Repeated lid evertion increased lid wiper staining (p = 0.007 when combined with double drop instillation). Light absorbance patterns and measured concentrations aligned with clinical findings. Conclusion: There were significant differences in performance between lissamine green solutions. Lid wiper staining was impacted by repeated lid evertion but sequential instillation and use of the Korb grading scale provided little advantage over simpler methods Clinicians must consider this when investigating lid wipers, especially when interpreting a negative finding.